1990
DOI: 10.3181/00379727-194-43081
|View full text |Cite
|
Sign up to set email alerts
|

Acetylsalicylic Acid Stimulates Murine Megakaryocyte Precursor Cells

Abstract: Depression of platelet function with a single intraperitoneal injection of acetylsalicylic acid was found to produce significant increases in several thrombocytopoietic indicators despite no observed change in platelet counts. There was an increase in the number of megakaryocytic precursor cells (small acetylcholinesterase positive or "SAChE+" cells), platelet size, and 35S incorporation into platelets. The results are qualitatively comparable to data from previous experiments showing that treatment of mice wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Mice given injections of aspirin showed a reduced maximum percentage of aggregation (58.7%), as compared with untreated control mice (69.1%). This finding agrees with the data of Sullivan and McDonald (6), which showed a significant reduction in aggregation of platelets at 8 hr after injections of aspirin and a reduced, but not significant, level of aggregation after 24 hr.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Mice given injections of aspirin showed a reduced maximum percentage of aggregation (58.7%), as compared with untreated control mice (69.1%). This finding agrees with the data of Sullivan and McDonald (6), which showed a significant reduction in aggregation of platelets at 8 hr after injections of aspirin and a reduced, but not significant, level of aggregation after 24 hr.…”
supporting
confidence: 93%
“…Box 1071, Knoxville, TN 37901-1071 of megakaryocyte precursor cells. the small acetylcholinesterase-positive (SAChE+) cells (6). In this work, poor platelet function was linked to increases in blood platelet production.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Because circulating platelet counts were also decreased in some CRF patients [5, 6], decreased thrombopoiesis has been associated with the pathogenesis of uremic bleeding. However, Sullivan and McDonald [7]found that platelet dysfunction is one of the stimulators of reactive thrombopoiesis, and later reports have actually demonstrated elevated serum thrombopoietin (TPO) levels in CRF patients [6, 8], suggesting increased thrombopoiesis in CRF, although it has not directly been examined in megakaryocytes, the site of thrombopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the inhibition of human megakaryocyte cyclooxygenase with low doses of aspirin is incomplete, and megakaryocyte cyclooxygenase seems to recover within 12 hours after aspirin ingestion 29,30 . Second, interruption of the platelet function by aspirin results in the production of new platelets, presumably through the action of a feedback system controlling thrombocytopoiesis 31 . With the newly formed platelets from the bone marrow in the absence of aspirin, these mechanisms may affect the platelet activity recovery time faster than the life span of the mature platelets.…”
Section: Discussionmentioning
confidence: 99%